A fluorescence biosensor based on single-stranded DNA and carbon quantum dots for acrylamide detection. (15th September 2021) - Wei, Qingyi; Zhang, Peiyao; Liu, Ting; Pu, Hongbin; Sun, Da-Wen
Highlights: A fluorescent biosensor for acrylamide (AM) detection was developed. High affinity between the DNA and AM ensured the specificity of the biosensor. A linear range with a low limit of detection was obtained. The biosensor showed good applicability for AM detection in bread crust. Abstract: As a potential carcinogen produced in food thermal processing, acrylamide (AM) can cause irreversible harm to human health. For the detection of AM in food products, a simple fluorescent biosensor based on single-stranded DNA (ssDNA) and carbon quantum dots (CQDs) was developed. Reduced fluorescence intensity of CQDs at 445 nm (excitation at 350 nm) was induced by the attachment of ssDNA. In the presence of AM, ssDNA was preferentially bound to AM by hydrogen bonding and the degree of fluorescence reduction was smaller than that without AM. Under optimized conditions, results showed that the sensing approach for detecting AM had a low detection limit of 2.41 × 10 −8 M in the standard solution, and a linear relationship ranging from 5 × 10 −3 to 1 × 10 −7 M with the determination coefficient (R 2 ) of 0.9895 was obtained. Furthermore, a good recovery percentage (91.36–98.11%) in bread crust showed the potential for practical applications of this proposed biosensor.